2008
DOI: 10.1080/00952990802013334
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Control Deficits in Childhood and Risk for Substance Use Disorders: A Review

Abstract: Identification of neurobiological factors that confer risk for the development of addiction may substantially advance development of new prevention and treatment strategies to combat substance use disorders. This review focuses on the relationship between impulsivity - a behavior that is common to the clinical picture of both substance use disorders (SUD) and childhood disruptive behavior disorders - and neurobiological risk for SUD. It further examines various behaviors within the over-arching domain of impul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 59 publications
3
62
0
4
Order By: Relevance
“…Studies of high-risk populations (e.g., a family history of alcoholism) suggest impairments in frontal functioning are apparent prior to drug use exposure (Monti et al 2005;Schweinsburg et al 2005) and can predict later substance use (Deckel and Hesselbrock 1996; see also Ivanov et al 2008 for a review). Schweinsburg et al (2005) demonstrated that on a Go/No-go fMRI paradigm, adolescents with a positive family history of alcoholism demonstrated less inhibitory frontal response than those with no family history, despite similar task performance between groups.…”
Section: Executive Control Dysfunction In "At-risk" Individualsmentioning
confidence: 99%
“…Studies of high-risk populations (e.g., a family history of alcoholism) suggest impairments in frontal functioning are apparent prior to drug use exposure (Monti et al 2005;Schweinsburg et al 2005) and can predict later substance use (Deckel and Hesselbrock 1996; see also Ivanov et al 2008 for a review). Schweinsburg et al (2005) demonstrated that on a Go/No-go fMRI paradigm, adolescents with a positive family history of alcoholism demonstrated less inhibitory frontal response than those with no family history, despite similar task performance between groups.…”
Section: Executive Control Dysfunction In "At-risk" Individualsmentioning
confidence: 99%
“…Disentangling the biological basis of substance misuse and ADHD symptoms has proven difficult previously because, for example, adult substance misusers are more likely to retrospectively endorse childhood ADHD symptoms (Ivanov et al, 2008). However, the results of Whelan et al (2012) suggest that ADHD symptoms and adolescent substance misuse can be separated, at least in terms of brain activity during a test of inhibitory control.…”
mentioning
confidence: 87%
“…Ces divers aspects de la personnalité sont hautement corrélés, en raison des nombreuses caractéristiques qu'ils partagent. Malgré un certain chevauchement entre les concepts, ces différents construits psychologiques proviennent de modèles dimensionnels composés de traits diversement structurés et reçoivent ainsi des définitions spécifiques (Aklin, Tull, Kahler, & Lejuez, 2009;Boyer & Byrnes, 2009;Holmes et al, 2009;Ivanov, Schulz, London, & Newcorn, 2008 (Xiao, 2008). D'autres auteurs parlent plutôt de propension à la prise de risques, qui est la tendance à s'engager de façon volontaire dans des activités susceptibles d'engendrer des conséquences négatives (Boyer, 2006;Holmes et al, 2009;Leigh, 1999;Magar et al, 2008).…”
Section: La Consommation De Psychotropes Et La Comorbidité Psychopathunclassified
“…Selon les connaissances actuelles, l'impulsivité représente un construit psychologique multidimensionnel, bien qu'il n'y ait pas d'unanimité quant aux différentes composantes (ou traits) qui le constituent (Chamberlain & Sahakian, 2007;de Wit, 2008;Holmes et al, 2009;Ivanov et al, 2008).…”
Section: La Consommation De Psychotropes Et La Comorbidité Psychopathunclassified
See 1 more Smart Citation